PENGARUH PRAPERLAKUAN JUS KUBIS BUNGA (Brassica oleracea L. var botrytis L.) TERHADAP AKTIVITAS DIKLOFENAK DALAM TERAPI INFLAMASI - Endang Sri Sunarsih; Dwi Hadi Setya Palupi; Indriati Hapsari (Majalah Obat Tradisional, 2011)
A drug therapy together with food consumption could influence the drug effectiveness. This research aimed to know the influence of cauliflower (Brassica oleracea L. var botrytis L.) juice pretreatment on diclofenac activity in inflammation therapy to wistar white male rats. Thirty rats divided into 6 groups randomized design. Group I (negative control) was only given aquadest, while group II (positive control) was given treatment with sodium diclofenac orally and the dose was 5,04 mg/kg BW. Group III was given pretreatment cauliflower juice with the dose of 20 ml/kg BW. It was given one hour before treatment with sodium diclofenac. Group IV was given pretreatment cauliflower juice with the dose of 20 ml/kg BW and it was given one day before treatment with sodium diclofenac. Group V was given pretreatment cauliflower juice with single dose 20 ml/kg BW for 3 days before treatment with sodium diclofenac,  and group VI was given pretreatment cauliflower juice with single dose 20 ml/kg BW for 5 days before treatment with sodium diclofenac. Thirty minutes after treatment with sodium diclofenac, the rat’s paw was injected with 1% carrageenan 0,10 ml subplantary. Edema volume was measured from 0th hour to 5th hour after carrageenan injection used the pletismometer. The result of statistic analysis of AUC and DAI data have shown that cauliflower juice pretreatment given one hour before treatment with sodium diclofenac did not show significant different with positive control. The research showed that cauliflower juice pretreatment for 3 and 5 days was capable to reduce antiinflamation activity of diclofenac, therefore inflammation therapy with diclofenac was not maximum.